Prediction sea level rise [SLR] rate and its' impact on coastal region of Perlis / Siti Nurnatasya Saidin - Saidin, Nurnatasya Saidin (2019)
The increment of sea level is increasing from time to time as can be proved by many studies from both local and global studies. This may be caused that the sea level rise will bring a huge impact on the land. For example, low-lying areas could have the potential to sink completely i f the sea level rise continues. This statement can be proved through many previous studies done. Therefore, the prediction o f rising sea level needs to be done accurately. This is important as a benchmark on possible dangers. The application of many geospatial technique in sea level rise rate and prediction enhance the ability o f survey field. In this study, altimeter data used to carry out the prediction of sea level rise. The usage o f altimeter data quite unfamiliar in our country although so many application can be done using it. With the prediction o f sea level rise, the authorities can plan efforts that can be taken to overcome the possible dangers. Using the map, areas exposed to the risk o f sea level rise can be further illustrated.